Aspirin Promotes Oligodendrocyte Precursor Cell Proliferation and Differentiation after White Matter Lesion - Chen, Jing; Zuo, Shilun; Wang, Jing; Huang, Jian; Zhang, Xiao; Liu, Yang; Zhang, Yunxia; Zhao, Jun; Han, Junliang; Xiong, Lize; Shi, Ming; Liu, Zhirong (Frontiers in Aging Neuroscience, 2014)
Cerebral white matter lesion (WML) is one of the main causes for cognitive impairment and is often caused by chronic cerebral hypoperfusion. A line of evidence has shown that aspirin has neuroprotective effects and produces some benefits in long-term outcome and survival for ischemic stroke patients. However, whether aspirin exerts a protective effect against WML is still largely unknown. Here, we showed that aspirin could promote oligodendrocyte precursor cell (OPC) proliferation and differentiation into oligodendrocytes after WML. Male Sprague-Dawley rats were subjected to permanent bilateral common carotid artery occlusion, a well-established model for WML. Four weeks later, Morris water maze test showed an impairment of learning and memory ability of rat while aspirin treatment improved behavioral performance. Low dose of aspirin (25 mg/kg) was found to elevate the number of OPCs while relatively high doses (100-200 mg/kg) increased that of oligodendrocytes, and ameliorated WML-induced the thinning of myelin, as revealed by the electron microscope. Similarly, our in vitro study also showed that relatively low and high doses of aspirin enhanced OPC proliferation and differentiation into oligodendrocytes, respectively. Furthermore, we revealed that aspirin enhanced extracellular signal-related kinase (ERK) but inhibited RhoA activities. In summary, we provided the first evidence that aspirin can promote oligodendrogenesis and oligodendrocyte myelination after WML, which may involve ERK and RhoA pathways.